Strip and tease: digitally undressing Tudor scribes - Craig-McFeely, J (National Library of Norway, 2021)
High-resolution digital images of our collections are reshaping our understanding of how we can approach and use damaged manuscripts. The most damaged sources can usually not be held or examined closely, but a very high quality digital image can serve as a literal surrogate, allowing us to access and even repair a damaged manuscript in a way that would otherwise be impossible. This way of interacting with manuscripts has radically changed the landscape of document research as well as the activities and functions of archives, libraries and scholars, and it has opened the door to some exciting advances in research. This paper discusses two very different approaches to manuscripts with extreme problems of legibility and access, examining the results and processes needed to tease out enough information by stripping back damage to achieve a usable result.